Evaluating the effect of using IP version and physical media on the ICMP throughput of a LAN - Dar, Humaira; Khan, Burhan ul Islam; Shah, Asadullah (Design for Scientific Renaissance, 2013)
Recently the world is witnessing a steady transition from IPv4 to IPv6 and Wireless has greatly emerged as the preferred technology than wired for LANs because the same provide expansive way for connecting hosts into the network. The main goal addressed in this paper is to evaluate the effect of using IPv4 and IPv6 over Wired and Wireless LAN setups on the ICMP based throughput of a LAN. Results are fetched by simulating wired and wireless LANs on Packet Tracer and a 22 experimental design technique has been employed for analysing results and drawing conclusions.